The Development of an Interactive E-Module with the Merdeka Curriculum Flow in Indonesian Language Learning in Elementary Schools - Hilabi, Abdurrahman; Ibrahim, A. Hanif (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study developed an interactive e-module based on the Merdeka Curriculum for teaching narrative texts to fifth-grade elementary students. Through a development process based on the ADDIE model, the e-module was evaluated as highly suitable in terms of content, design, and operation by media, material, and language experts. Trials with students showed that the e-module effectively improved students’ ability to understand the concept of narrative texts. The results of this study indicate that the e-module can be an effective and efficient learning medium to support Indonesian language learning in elementary schools.